Effect of pressure and stacking method on combustion characteristics of paper stacks - Chao Ding; Zijian Yan; Yuyao Li; Lingfeng He; Shuangyang Ma; Xingzhao Wang; Que Huang; Yan Jiao; Changcheng Liu (Case Studies in Thermal Engineering, 2022)
The experimental study on the combustion characteristics of paper stack fires was carried out in a low-pressure chamber. The variability of which with different environmental pressures and stacking methods were investigated. The mass of each group of experimental paper strips was 107 g. Three iron frames had the same volume, but different lengths and widths, and the strips were placed evenly in the frames to simulate different ways of paper stacking. The combustion tests of the paper stack were conducted at four ambient pressures of 101 kPa, 80 kPa, 60 kPa, and 40 kPa, respectively. The parameters measured during the experiments included mass loss, heat release rate (HRR), and flame temperature. The experimental results showed that the stacking type and pressure significantly affected the properties of the paper stack fire. For instance, the burning rate was influenced by the cross-sectional combustion area, pressure, and load height. There was a linear relationship between the ratio of the peak burning rate to the characteristic length of the bottom surface and the pressure-load height. The intensity factor of the paper stack fire was closely related to the environmental pressure: the paper stack fire under atmospheric pressure was generally a fast-growing one, which was a medium-growing fire under about 80 kPa. In comparison, that was a slow-growing fire when the pressure was 60 kPa.